History Of Crafts And Its Types - Rakhmatova Mavjuda (Genius Journals, 2024)
This article talks about the history of crafts and its types. Based on scientific data, the author studied and analyzed the history of crafts and its specific aspects based on available literature.
Keywords: Crafts; history; culture; types of crafts